Impacto das classificações de rating no valor das empresas brasileiras - Augusto, Danilo (2015)
The present study examines how the announcements of credit rating changes affect the market value of the Brazilian companies. It was considered the announcements made in a period of 3 years for the universe of companies that integrate the Bovespa equity index. The methodology chosen is the Event Study, using the Market Model to estimate the equity normal returns for a 1 year estimation window. The conclusion is that the announcements have influence in the price of the equities and that this effect is stronger in the case of ratings decrease announcements (downgrades): investors tend to anticipate the downgrade announcements as the accumulate return of equities is negative before the date of the announcement and positive after it. This conclusion is similar to the ones that studies using American and European equities have made. Another conclusion was that separating the downgrades sample into investment grade and non-investment grade companies, the effect of the ratings disclosure is more pronounced in the second group.